A Multiagent System for Urban Traffic Control - Batista Júnior, Antonio de Abreu; Coutinho, Luciano Reis (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC); 2013: Anais do VII Workshop-Escola de Sistemas de Agentes, seus Ambientes e AplicaçõesDO - 10.5753/wesaac.2013.33168, 2013)
In this paper we propose a multiagent system (MAS) – designed as a social organization – to operate in the control of successive signals along a section of an avenue that combines green wave and adaptive control in a dynamic way. The members of this organization represent traffic agents that communicate among themselve via a specific purpose interaction protocol. On the one hand, the coordination of successive signals is achieved dynamically through standardized communication between organizational roles. On the other hand, the adaptive control is achieved by the independent and autonomous actions of the agents that make up the organization. We test our approach in simulation. The results show that our approach result in good performance, achieving both local control at the intersections as well as coordination of successive intersections.